The spirit / Mastura Mohd Jarit - Mohd Jarit, Mastura (Faculty of Art and Design, 2021)
This research intends to ascertain design and development utilizing the expressive use of typographic styling. It also intends to identify the relationship of types used in the design as related to communication and environment. Primarily, a concept and idea should be developed for such a unique typography. To propose a concept, we basically need to include and understand as many elements as we can which directly or indirectly involve things such as environment, lifestyle, social, economic, politic etc. In addition to that, emotion and audience characters will be added in for the audience to feel the message. The unique typefaces basically are the ideas from Jawi writing known as early as Malay writing. The typefaces carry the personality of Jawi character which is influenced from Arabic writing. The Arabic writing follow the law of Islam that carry the understanding of Al-Quran which instruct humankind in the value of goodness, comfort, prosperity and elegance. Islamic art also stands against all forms of polytheism. The detailed investigations into typefaces and letter font has led to their appropriateness within commercial art and the choices of typefaces in design, the importance of type and of choosing the right typefaces.